2002
DOI: 10.1097/00001756-200210280-00011
|View full text |Cite
|
Sign up to set email alerts
|

Think differently: a brain orienting response to task novelty

Abstract: Cognitive flexibility hinges on a readiness to direct attention to novel events, and on an ability to change one's mental set to find new solutions for old problems. Human event-related potential (ERP) studies have described a brain 'orienting' response to discrete novel events, marked by a frontally distributed positive potential peaking 300-400 ms post-stimulus (P3a). This brain potential has been typically related to bottom-up processing of novel non-targets under a fixed task-set (i.e., press a button to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
181
5
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(224 citation statements)
references
References 22 publications
28
181
5
8
Order By: Relevance
“…The hypothesis that phasic NE reports on the ratio between posterior probability and prior probability of a task state is consistent with the well-known sensitivity of the P3 to (subjective) prior probability (e.g., Daffner et al, 2000;Squires, Wickens, Squires, & Donchin, 1976; see also Barceló, Periáñez,& Knight, 2002). For example, P3 amplitude is highly sensitive to expectations elicited by the recent stimulus-sequence history in an oddball task: the P3 to an oddball target stimulus is larger when the target stimulus is preceded by a series of nontarget stimuli than when it is preceded by a series of other targets (Squires et al, 1976;but see Holm, Ranta-aho, Sallinen, Karjalainen, & Müller, 2006).…”
Section: ) the Relationship Between The P3 And Learningsupporting
confidence: 83%
“…The hypothesis that phasic NE reports on the ratio between posterior probability and prior probability of a task state is consistent with the well-known sensitivity of the P3 to (subjective) prior probability (e.g., Daffner et al, 2000;Squires, Wickens, Squires, & Donchin, 1976; see also Barceló, Periáñez,& Knight, 2002). For example, P3 amplitude is highly sensitive to expectations elicited by the recent stimulus-sequence history in an oddball task: the P3 to an oddball target stimulus is larger when the target stimulus is preceded by a series of nontarget stimuli than when it is preceded by a series of other targets (Squires et al, 1976;but see Holm, Ranta-aho, Sallinen, Karjalainen, & Müller, 2006).…”
Section: ) the Relationship Between The P3 And Learningsupporting
confidence: 83%
“…In turn, shift 2D cues evoked larger P3a potentials than stay 1 cues (P < 0.003; Figure 3). Stay 2 and later trials evoked similar brain responses in both type A and B series [3,4]. Finally, P3a amplitudes to shift 3D cues did not diminish over successive task blocks, consistent with behavioural evidence that set shifting costs do not decline with practice [20].…”
Section: Erps and Data Analysissupporting
confidence: 74%
“…This has led to a more comprehensive ERP analysis of both contextual processes time-locked to feedback events, and target-related processes time-locked to the card-matching stage of task performance (see Figure 1b). This novel ERP paradigm shows that task-switching consists of several cognitive processes, as reflected by a number of ERP components, the most conspicuous of which is the endogenous P300 response [4]. Therefore, the MCST task-switching protocol represents a new and promising tool for examining the putative relationship between attention set-shifting and the frontal (P3a) and posterior (P3b) components of the P300 response system.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have reported that in comparison with task repeat trials, there was a switch-related central-posterior positivity occurring about 400 ms after the cue (Hsieh, 2002;Karayanidis, Coltheart, Michie, & Murphy, 2003;Miniussi, Marzi, & Nobre, 2005;Moulden et al, 1998;Rushworth, (Slagter, Kok, Mol, Talsma, & Kenemans, 2005). This positivity was interpreted by some authors as P3b modulation (Barceló, Periáñez, & Knight, 2002;Kieffaber & Hetrick, 2005;Nicholson, Karayanidis, Poboka, Heathcote, & Michie, 2005;Tieges, Snel, Kok, Plat, & Ridderinkhof, 2007) and by others as a reduction in CNV (Hsieh & Chen, 2006;Lorist et al, 2000). The posterior positivity is sometimes preceded by an early (100 to 300-ms) or moderately early (300 to 500-ms) anterior positivity (Astle, Jackson, & Swainson, 2008;Rushworth et al, 2002) or followed by a late (500 to 1,000-ms) anterior negativity (Astle et al, 2008;Lavric, Mizon, & Monsell, 2008;Moulden et al, 1998).…”
mentioning
confidence: 98%
“…Of interest here is the suggestion that the modulation of the P3b ERP component (e.g., Barceló et al, 2002;Gehring, Bryck, Jonides, Albin, & Badre, 2003;Hsieh & Chen, 2006;Karayanidis et al, 2003;Kieffaber & Hetrick, 2005;Wylie, Javitt, & Foxe, 2003) represents the inhibition of the task set as a whole (Hsieh & Liu, 2008. Among these studies is Hsieh and Liu's (2009) study that was described beforehand.…”
mentioning
confidence: 99%